Blending Spaces: Cross-Reality Interaction Techniques for Object Transitions Between Distinct Virtual and Augmented Realities - Cools, Robbe; Esteves, Augusto; Simeone, Adalberto L. (2022 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2022)
Cross-Reality (CR) involves interaction between different modalities and levels of immersion such as Virtual and Augmented Reality, as we explore in this paper. Whereas previous work assumed similarity between their respective Virtual and Augmented Environment (VE and AE), we explore the case in which VE and AE are distinct. This gives rise to novel and critical problems, such as how to visualise and interact with the other environment. In this context we investigate the fundamental interaction of transitioning an object across environments, to which we contribute five interaction techniques. Two are inspired by literature: Virtual Magic Lens and Binary Transition; while the other three are entirely novel: Auto Blended Space, Manual Blended Space - Button Transition and Manual Blended Space - Touch Transition. In a study evaluating the first four techniques, we found that participants (N=20) performed a CR object manipulation and transition task significantly faster using our Auto Blended Space technique. We then modified Manual Blended Space - Button Transition into Manual Blended Space - Touch Transition in response to these results, and reassessed the four techniques in a more complex object manipulation task (N=16). We found that this type of task was better suited to manual transition methods rather than automatic methods. Taken together, our final contribution are five blended space design factors, and timely Cross-Reality transition design guidelines.